A transformação digital e a sua relação com a reestruturação dos processos de negócio no SEBRAE/RN - Silva, Luis Felipe dos Santos (2019)
Digital transformation is a constant in the businesses of the 21st century, regardless of its segment and size. Digital transformation is not only about adopting incremental technologies, but to build the foundation of the companies in a process-oriented manner, including the people while changing the organizational culture in order to face a new and digital world. To face the obstacles in the process of change must become an ordinary task for the companies built-in the strategies, aiming the transition from a conventional to a digital model. This study aims to investigate the importance of investing in people and the restructuring processes, with a focus on making them more agile, innovative, collaborative, strategic and digital. Redesigning processes adhering to best practices and new concepts is critical to the vitality and longevity of any company. For this, we carried out a bibliographical research to establish the main concepts involved. Later on, data were collected through interviews and observation in order to provide sufficient information for the analysis, searching for the relationship between digital transformation and business process restructuring. The main impact for companies is the difficulty of predictability and planning, after all, the world is uncertain, volatile, complex and ambiguous. But to become digital is to understand that the answers given to the market today may not be sufficient for the demands of tomorrow. Therefore, adapting to the current situation of the digital market is vital, and to make this an ordinary process is needed so the company becomes able to respond to each demand that the clients and the market presents.